2007
DOI: 10.4064/fm197-0-11
|View full text |Cite
|
Sign up to set email alerts
|

Topology and dynamics of unstable attractors

Abstract: Abstract. This article aims to explore the theory of unstable attractors with topological tools. A short topological analysis of the isolating blocks for unstable attractors with no external explosions leads quickly to sharp results about their shapes and some hints on how Conley's index is related to stability. Then the setting is specialized to the case of flows in R n , where unstable attractors are seen to be dynamically complex since they must have external explosions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 11 publications
0
30
0
Order By: Relevance
“…An instance of this fact was presented in [27,Theorem 17], where it was shown that every connected unstable attractor in R n must have external explosions. Let us remark here that, although this approach is inscribed in the lines of the classical work by Morse, Smale and Conley, it is not subsumed in it.…”
Section: Manifolds Which Contain Attractors With No External Explosionsmentioning
confidence: 95%
See 2 more Smart Citations
“…An instance of this fact was presented in [27,Theorem 17], where it was shown that every connected unstable attractor in R n must have external explosions. Let us remark here that, although this approach is inscribed in the lines of the classical work by Morse, Smale and Conley, it is not subsumed in it.…”
Section: Manifolds Which Contain Attractors With No External Explosionsmentioning
confidence: 95%
“…(2) By [27, Lemma 3] K possesses a neighbourhood basis of isolating blocks N with the property that N = N + ∪ N − (we refer the reader to [27] for a detailed discussion of isolating blocks for attractors with only internal explosions). We shall prove that any of them has the features described in the statement of the lemma.…”
Section: Attractors With No External Explosions Definition and Basicmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown in [18] and [23] that there exists manifolds M which cannot contain unstable attractors without external explosions, or otherwise stated every isolated connected attractor in M is either stable or has external explosions. The next corollary goes in the same line but it is applicable to arbitrary phase spaces.…”
Section: Attractors Revisitedmentioning
confidence: 98%
“…Proposition 4.1 means that the simplest unstable attractors are those whose explosion points lie all in K. These receive a special name, first introduced by Athanassopoulos in [1]: an attractor with no external explosions is an attractor K such that J + (p) ⊆ K for all p ∈ A(K) − K. They have been studied in [1], [18] and [23] when M is a manifold, and we will see that many of the results contained in those papers still hold for more general phase spaces. The reasons why this generality is of interest are presented at the end of the section.…”
Section: Proposition 41 If An Attractor K Is Unstable There Are Expmentioning
confidence: 98%